2017
DOI: 10.1371/journal.pntd.0005652
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-targeted and case-triggered use of a single dose of oral cholera vaccine in an urban setting: Feasibility and vaccine coverage

Abstract: IntroductionIn June 2015, a cholera outbreak was declared in Juba, South Sudan. In addition to standard outbreak control measures, oral cholera vaccine (OCV) was proposed. As sufficient doses to cover the at-risk population were unavailable, a campaign using half the standard dosing regimen (one-dose) targeted high-risk neighborhoods and groups including neighbors of suspected cases. Here we report the operational details of this first public health use of a single-dose regimen of OCV and illustrate the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 20 publications
0
63
0
Order By: Relevance
“…Because of this, the use of a single dose has been proposed as a temporising measure to reduce cholera risk in the short term, leading to an interest in understanding the protective effect of a single dose of oral cholera vaccines. 17 , 18 One modelling study suggested that the one-dose approach could avert more cholera cases by generating greater herd immunity relative to what could be achieved by vaccinating fewer people with two doses; however, these findings were based on scarce short-term single-dose efficacy data. 19 Our estimates of single-dose effectiveness appeared higher or extended, or both, relative to those previously reported; however, confidence intervals around our estimates were wide owing to a relatively small number of individuals who received a single dose (ie, we aimed to give everyone in the campaign two doses).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, the use of a single dose has been proposed as a temporising measure to reduce cholera risk in the short term, leading to an interest in understanding the protective effect of a single dose of oral cholera vaccines. 17 , 18 One modelling study suggested that the one-dose approach could avert more cholera cases by generating greater herd immunity relative to what could be achieved by vaccinating fewer people with two doses; however, these findings were based on scarce short-term single-dose efficacy data. 19 Our estimates of single-dose effectiveness appeared higher or extended, or both, relative to those previously reported; however, confidence intervals around our estimates were wide owing to a relatively small number of individuals who received a single dose (ie, we aimed to give everyone in the campaign two doses).…”
Section: Discussionmentioning
confidence: 99%
“… 12 This strategy was first used under field conditions in 2015, in Juba, the conflict-ravaged capital of South Sudan, when more than 160 000 people were vaccinated in response to a cholera outbreak. 11 In a short-term observational study, the effectiveness of a single dose of vaccine in this campaign in Juba was estimated to be 87.3% (95% confidence interval, CI: 70.2–100.0). 13 In 2014, a clinical trial in Bangladesh indicated that a single dose of oral cholera vaccine would give 40% (95% CI: 11–60) and 63% (95% CI: 24–82) protection against all and severe episodes of cholera, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Other possible challenges are inadequate financial and human resources and inadequate number of doses to target everyone at risk of cholera, especially for a multi-dose campaign. 11 While the licensed protocol requires two doses of oral cholera vaccine to be given two weeks apart, the feasibility of such a regimen has been, and remains, limited by the availability of suitable vaccines doses. Given a global shortage of such vaccines, a single-dose strategy, which, given a fixed number of doses, could cover twice as many people as a two-dose regimen, should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…These teams can quickly provide emergency water, sanitation and hygiene interventions (e.g., point of use water treatment and basic hygiene educational materials), and sometimes oral cholera vaccine to neighbors of cholera cases. 6, 7 However, limited evidence exists regarding the impact or optimal spatial scale of these targeted interventions.…”
Section: Introductionmentioning
confidence: 99%